Non-Bragg band gaps in 1D metamaterial aperiodic multilayers - Monsoriu, Juan A. (2007)
We investigate the existence of non-Bragg band gaps in 1D aperiodic photonic structures, namely the Fibonacci and Thue-Morse lattices combining ordinary positive index materials and dispersive metamaterials. Both structures present new band gaps which, in contrast with the usual Bragg gaps, are not based on interference mechanisms. One of these non-Bragg gaps, called zero-n -n gap and corresponding to zero (volume) averaged refractive index, has been reported to be present in Fibonacci lattices. In this paper we extend this result to other aperiodic systems, showing the existence of a zero-n gap also in Thue-Morse lattices. Furthermore, we show that these systems can also support two polarization-selective non-Bragg gaps: the zero permeability, and the zero permittivity gaps. Some distinctive aspects of these gaps are outlined and the impact on the photonic spectra produced by the level of the generation of the aperiodic structure is analyzed.